Eksperimen Model Pembelajaran Problem Based Learning Berbasis Penilaian Portofolio Ditinjau Dari Kemandirian Belajar Siswa Kelas Viii Smp Negeri 3 Sawit Tahun Ajaran 2016/2017 - Setyadi, Tommy Yoga; , Muhammad Noor Kholid, S.Pd, M.Pd (2017)
This research aims to determine: (1) the differences effect of learning model of problem based learning of assessment portfolio based, learning model of problem based learning, and learning model of expository for mathematics learning outcome, (2) the differences effect of the level of independent learning for mathematics learning outcome, (3) the interaction between learning model and independent learning for mathematics learning outcome. The type of the research is experiment with quasi experimental design. The population of the research was all students of VIII Grade of SMP N 3 Sawit of even semester of academic year 2016/2017. The research sample consisted of three classes, experiment class I treated problem based learning of assessment portfolio based, experiment class II treated problem based learning, and control class treated expository. The sampling technique use cluster random sampling. Methods of data collection use documentation, questionnaire, and test. Data analyzed by analysis of variance with two different cell lines with a significance level of 5%. Based hypothesis testing, we concluded that: (1) there is differences effect of learning model of problem based learning of assessment portfolio based, learning model of problem based learning, and learning model of expository for mathematics learning outcome, (2) there is differences effect of the level of independent learning for mathematics learning outcome, (3) there is no interaction between learning model and the level of independent learning for mathematics learning outcome.